THE INSHOT- ASSISTED INQUIRY LEARNING MODEL ON STUDENTS' SCIENCE PROCESS SKILLS ON THE MAIN MATERIAL OF WORK AND ENERGY IN GRADE X MIPA IN THE EVEN SEMESTER OF GAJAH MADA MANDIRI PRIVATE SENIOR HIGH SCHOOL MEDAN IN THE 2022/2023 ACADEMIC YEAR - Gita (Jurnal Edukasi dan Pembelajaran STEM, 2025)
This study aims to determine the significant effect of the use of the inshot-assisted inquiry learning model using the main material of work and energy in class X MIPA, even semester, Gajah Mada Mandiri Private High School, Medan, Academic Year 2022/2023. This kind of research is basically experimental. All students of class X MIPA, even semester, Gajah Mada Mandiri Private High School, Medan from both classes constitute the majority of the population in the essay. Cluster random sampling was used to collect samples, with X MIPA1 and X MIPA2 acting as the experimental and control groups, respectively, with a total of 32 participants each and a teaching model that emphasizes in-depth learning with short lessons. The instrument used in this study was an essay test with approximately 10 validated topics. Data analysis of Lhitung-Ltabel and Fhitung-Ftabel showed that both data sets had a normal and homogeneous distribution. Analysis of two similar government agencies will be carried out next. The results of both classes were normally and uniformly distributed. Because tcount > ttable, the results of the one-tailed t-test for alpha = 0.05 and dk 62 produced tcount = 21.27 and ttable 1.99. This shows that there are significant benefits from using interdisciplinary learning with an inquiry model to support the student process in semester X of Mathematics and Natural Sciences in the academic year 2022/2023.